ANALISIS KEPUASAN KONSUMEN PADA TOKO MU (STUDI KASUS PADA PEGAWAI UNIVERSITAS MUHAMMADIYAH KOTABUMI) - Deska Safitri; Sri Puji Lestari; Yuni Elmita Sari; Aji Setiya Bakti (Universitas Muhammadiyah Kotabumi, 2023)
Minimarkets are a place to buy basic necessities. Some people prefer to shop at minimarkets because, apart from being easily accessible, they are also a place to shop that is considered quite comfortable. Seeing this opportunity, the North Lampung Muhammadiyah regional leadership also established a minimarket with the Toko MU brand. However, the service at Toko MU is considered to be still not good when compared to other minimarkets, especially minimarkets with a franchise system. The aim of this research is to analyze the level of consumer satisfaction at Toko MU based on service, price, product, and store access factors to find out what attributes are priorities. improving customer satisfaction at MU Stores and providing suggestions for priority improvements for MU Stores to increase customer satisfaction. The method used is a quantitative method. Data was collected using a questionnaire, and data measurement used a Likert scale. The number of respondents was 100, who were consumers at the MU Store located in the Muhammadiyah University Kotabumi area. This research uses the Customer Satisfaction Index (CSI) data analysis method, with the level of consumer satisfaction being